Organic Coffee Supply Chain Source Process Integration: A Peruvian Case - Edgar D. Ramos; Daniel Matos; Sara Ruiz; Ron Mesia (International Journal of Supply Chain Management, 2019)
This paper analyzes the Supply Chain (SC) of the Coffee Industry, for organic production and develops the relationship between Supply Chain Management (SCM) and Supply Chain Integration (SCI) with the performance of Cooperatives and Coffee Associations in Junin Region, Peru. It also analyzes the current scenario of the Coffee Sector and the participation of the SC in the processing and distribution of Organic Coffee in Junn, Peru. A diagnosis process was made in the certified organizations belonging to the market, through results obtained from surveys and interviews that were applied in the sample space; this diagnosis indicated that they do not have a correct flow of information and materials, and evidenced the low level of interactions between the members; all this related to the SC. The final objective of this research is to improve the competitiveness of the organizations through the increase in the performance of the SC, for which a model of Integration appropriate to reality is proposed